ANALISIS PENGUJIAN ARUS BOCOR LINE POST INSULATOR 70 kV YANG TERKONTAMINASI POLUTAN INDUSTRI - Kamil Amali, Lanto Mohamad (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
Failure of Insulators of ‘Line Post Insulator 70 kV type’ usually caused by many factors, such as the leakage current on contaminated insulator surfaces. This leakage current will cause interference with the electrical energy distribution system. This study reported the results of testing the leakage current on insulator 70 kV Line Post Insulator type  performed on high-voltage laboratory Ujung Pandang State Polytecchnics. Based on testing, the maximum leakage current value obtained in wet conditions polluted with spraying of pollutants ESDD = 3.2 mg/cm2 and NSDD =  0.08 mg/cm2 with a value of leakage current of 7.4 mA at an applied voltage of 22 kV, this can result in flashover. Keyword : Insulator, Current leakage, Flashover